Telaah Kesadaran dan Kepatuhan Hukum Pengguna Jalan terhadap Rambu Larangan Putar Balik: Studi Kasus di Jalan Nasiolal (Jalan Magelang), Sleman - Isnawan, Fuadi (Universitas Muhammadiyah Surabaya, 2025)
Violations of no-u-turn signs are a traffic law issue that affects order, safety, and the effectiveness of transportation policies in public spaces. This study aims to analyze the factors that cause violations and the efforts made to address them, with a case study on Jalan Magelang Km 7.5 and Km 8.5, Sleman, Yogyakarta. This study uses an empirical legal method. The results of the study indicate that there are three main factors driving violations. First, the distance between the no-turn zone and the official U-turn location is considered too far by road users. Second, time efficiency considerations drive rational decision-making despite being contrary to the law. Third, the role of traffic volunteers (supeltas) socially legitimizes violations by signaling safe U-turns at prohibited locations. On the other hand, efforts to address violations are carried out through three main strategies: police presence during peak violation hours as a form of prevention and direct law enforcement, a persuasive approach through on-site education for violators, and the installation of road barriers as a physical intervention to block access to illegal U-turns. These three efforts not only represent repressive actions but also illustrate structural and educational strategies aligned with situational crime prevention theory, deterrence theory, and community policing. The research findings emphasize that effective law enforcement cannot rely solely on penalties but must also consider technical, social, and cultural aspects of society to foster sustainable compliance with the law.